2014
DOI: 10.1016/j.biortech.2014.02.071
|View full text |Cite
|
Sign up to set email alerts
|

Selecting low-cost carbon sources for carotenoid and lipid production by the pink yeast Rhodosporidium toruloides NCYC 921 using flow cytometry

Abstract: h i g h l i g h t sCarop pulp syrup (CPS) and sugarcane molasses (SCM) were used as carbon sources. CPS at 75 g L À1 induced the highest fatty acid and carotenoid productivities. Flow cytometry detected differences between the cell membrane grown on CPS and SCM. R. toruloides growth on CPS induced lower ratio of permeabilised cells than on SCM. a r t i c l e i n f o b s t r a c tThe present work studied low-cost carbon sources for carotenoid and lipid production using the yeast Rhodosporidum toruloides NCYC 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 13 publications
3
35
0
5
Order By: Relevance
“…The closest species genetically to those studied in this work are Rhodotorula and Rhodosporidium (97%), both characterized as lipid and carotenoid producers (Saenge et al 2011, Freitas et al 2014. A more distant similarity (81%) was found with species of the Thraustochytriaceae family, characterized by high levels of DHA production (Chi et al 2007).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The closest species genetically to those studied in this work are Rhodotorula and Rhodosporidium (97%), both characterized as lipid and carotenoid producers (Saenge et al 2011, Freitas et al 2014. A more distant similarity (81%) was found with species of the Thraustochytriaceae family, characterized by high levels of DHA production (Chi et al 2007).…”
Section: Discussionmentioning
confidence: 56%
“…Rhodosporidium toruloides and Rhodotorula glutinis produce around 70 and 33.7% of total lipids in dry weight, respectively. However, the fatty acids produced by these species include myristic, palmitic, palmitoleic, steric, oleic, linoleic and -linoleic acids (Li et al 2006, Freitas et al 2014, in contrast to the strains studied here that produce high concentrations of DHA and EPA, neither of which have been described in Rhodotorula and Rhodosporidium (Li et al 2007, Hu et al 2009). …”
Section: Discussionmentioning
confidence: 80%
“…They showed that the overall biodiesel production cost was economically competitive (US$ 0.76/l) to that of vegetable biodiesel (US$ 0.81/l) and the yield of biodiesel is 6.3-fold higher (4172 l/ha of cultivated sugarcane) than that obtained from yield of soybean biodiesel (661 l/ha of cultivated soybean) [65]. Besides this various low-cost raw materials such as sugarcane molasses (SCM) are extensively used as raw materials for oleaginous yeast due to its availability and high sugars contents [66]. It has been earlier reported that Rhodosporidium toruloides could produce 63.2% and 56.5% lipid content (w/w) when hydrolysates of non-edible crops Cassava and Jerusalem artichoke respectively were provided [67].…”
Section: Low-cost Substrates Utilized By Oleaginous Yeasts To Producementioning
confidence: 99%
“…In particular, red yeasts of the genera Phaffia, Rhodotorula and Sporidibolus exhibit production of considerable amounts of carotenoids (Davoli et al, 2004;Dias et al, 2016), rendering these yeast strains potential sources for industrial pigment production (Freitas et al, 2014;Yen and Chang, 2015).…”
Section: Introductionmentioning
confidence: 99%